Auf dem Weg zu einem Urheberrecht für das 21. Jahrhundert: Ideen für eine zukünftige Regulierung kreativer Güter - Till Kreutzer (Wirtschaftsdienst, 2012)
Moderne Technologien machen es den Nutzern möglich, sehr viel mehr urheberrechtlich geschützte Güter zu kopieren und weiterzugeben, als dies noch vor 50 Jahren der Fall war. Das Urheberrecht kann die Rechteinhaber derzeit nicht effektiv schützen. Es müsste gründlich reformiert werden, um Kreativen zu ihrem Recht, das weniger durch Privatnutzer als vielmehr von Verwertern beschnitten wird, zu verhelfen. – – The article describes the challenges of copyright protection in the digital world. Starting from the observation that copyright is one of the most disputed regulative systems in the 21st century, it analyses the reasons for the intensity of the public and political debate. The analysis comes to the conclusion that the main reason for this is the radical change of impact copyright law has undergone since computers and Internet access found their way into almost every household. What was designed as a regulative system for professional market players became a statutory code of conduct for the general public. However, the necessary steps to acknowledge this elementary change were never taken by the legislators. The article concludes that a copyright that affects professional authors, rights holders, prosumers and consumers alike needs significant conceptual modifications. Several proposals for short-, middle- and long-term changes of the copyright systems are offered.
Keywords: D23; K11; O34; 330; Urheberrecht; Internet; Sozialer Wandel; Digitale Güter; Immaterialgüterrechte; Welt